2022
DOI: 10.3389/fnagi.2022.923560
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant gray matter volume and functional connectivity in Parkinson’s disease with minor hallucination

Abstract: Background: Minor hallucination (MH) is the most common psychotic symptom in Parkinson's disease (PD); it can develop into well-structured visual hallucination (VH), suggesting that MH may be a staccato form of wellstructured VH. However, it remains unclear whether the pathogenesis is the same. Therefore, the aim of this study was to investigate the altered gray matter volume (GMV) and functional connectivity (FC) of MH in PD to further understand the complex mechanisms. Materials and methods:We included 67 PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…Some disparities could be attributed to the limited number of our patient samples. The overlap results emphasize the signi cant appearance of gray matter reduction in the superior temporal gyrus, coherent with previous research ndings 5,[27][28][29] . Abnormalities in this region have been linked with key symptoms of PD, including theory of mind impairment, apathy, cognitive impairment, depression, freezing of the gait, and frequent falls [30][31][32][33] .…”
Section: Discussionsupporting
confidence: 91%
“…Some disparities could be attributed to the limited number of our patient samples. The overlap results emphasize the signi cant appearance of gray matter reduction in the superior temporal gyrus, coherent with previous research ndings 5,[27][28][29] . Abnormalities in this region have been linked with key symptoms of PD, including theory of mind impairment, apathy, cognitive impairment, depression, freezing of the gait, and frequent falls [30][31][32][33] .…”
Section: Discussionsupporting
confidence: 91%
“…The remaining associations with illusory responses are consistent with previous findings, including processing speed, language (both visually based naming and fluency), and visual memory 49 . Our results lend additional support to the hypotheses that visual hallucinations (even minor illusory phenomena) may occur due to some combination of visual information processing, attention deficits or disruptions to attention networks, and/or disruptions in the default mode network 50–54 . To date, there is a lack of clear understanding of the timing and relative importance of these changes, as well how deficits in language may fit with current models.…”
Section: Discussionsupporting
confidence: 89%
“…49 Our results lend additional support to the hypotheses that visual hallucinations (even minor illusory phenomena) may occur due to some combination of visual information processing, attention deficits or disruptions to attention networks, and/or disruptions in the default mode network. [50][51][52][53][54] To date, there is a lack of clear understanding of the timing and relative importance of these changes, as well how deficits in language may fit with current models. Given this, and that our results are in a relatively small sample and do not hold up to multiple comparisons testing, further exploration into domain-specific relationships between pareidolias and cognitive performance is needed to provide insight into common underlying pathways between psychosis and specific cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…Although only a few articles have been published on imaging studies of MHs, several similar structural and functional characteristics between MHs and VHs have been found. Apart from gray matter atrophy in limbic and paralimbic regions in patients with VHs ( Lenka et al, 2015 ), morphometric studies also reported reduced gray matter volume of posterior cingulate cortex and parahippocampal gyri in patients with MHs ( Bejr-Kasem et al, 2019 ; Zhong et al, 2022 ). Considering that RBD represents a more aggressive PD subtype ( Fereshtehnejad et al, 2015 ), we conjecture that MHs in this population may be associated with damage to related brain regions in the early stage.…”
Section: Discussionmentioning
confidence: 99%